Image analysis for composition monitoring. Commercial blends of olive and soybean oil - doi: 10.4025/actascitechnol.v35i2.15216 - Fernandes, Jessica Kehrig; Umebara, Tiemi; Lenzi, Marcelo Kaminski; Silva, Ediely Teixeira (Acta Scientiarum. Technology, 2012)
Olive oil represents an important component of a healthy and balanced dietary. Due to commercial features, characterization of pure olive oil and commercial mixtures represents an important challenge. Reported techniques can successfully quantify components in concentrations lower than 1%, but may present long delays, too many purification steps or use expensive equipment. Image analysis represents an important characterization technique for food science and technology. By coupling image and UV-VIS spectroscopy analysis, models with linear dependence on parameters were developed and could successfully describe the mixture concentration in the range of 0-100% in mass of olive oil content. A validation sample, containing 25% in mass of olive oil, not used for parameter estimation, was also used for testing the proposed procedure, leading to a prediction of 24.8 Â± 0.6. Due to image analysis results,Â 3-parameter-based models considering only R and G components were developed for olive oil content prediction in mixtures with up to 70% in mass of olive oil, the same test sample was used and its concentration was predicted as 24.5 Â± 1.2. These results show that image analysis represents a promising technique for on-line/in-line monitoring of blending process of olive soybean oil for commercial mixtures. Â